Physiologically Based Pharmacokinetics Model in Pregnancy: A Regulatory Perspective on Model Evaluation - Coppola, Paola; Kerwash, Essam; Cole, Susan (Frontiers in Pediatrics, 2021)
Physiologically based pharmacokinetics (PBPK) modelling is widely used in medicine development and regulatory submissions. The lack of clinical pharmacokinetic data in pregnancy is widely acknowledged, therefore one area of current interest is in the use of PBPK modelling to describe the potential impact of anatomical and physiological changes during pregnancy on the medicine’s pharmacokinetics. PBPK modelling could possibly represent a predictive tool to support the medicine benefit‐risk decision and inform dose adjustment in this population and also to investigate medicine levels in the foetus to support the risk assessment to the foetus. In the contest of regulatory application, there are however a number of considerations around model evaluation, and this should be tailored to the model purpose, in order to inform the confidence in the model for the intended application. A number of gestational age-related physiological changes are expected to alter the pharmacokinetics of medicines during pregnancy, and there are uncertainties on some parameters, therefore well qualiﬁed models are needed to improve assurance in the model prediction before this approach can be used to inform with confidence high impact decisions as part of regulatory submissions.